Physical characteristics of water paint with the addition of bintaro extract additives - Syahputra, Romi Fadli; Wulandari, Surya; Ginting, Delovita (Indonesian Physics Communication, 2024)
The addition of additives to paint aims to improve the quality and usability of paint. Natural additives, such as bintaro seed extract, have potential as anti-bacterial and anti-fungal agents. This study aims to investigate the physical properties of commercial paints added with bintaro seed extract. The physical properties tested were changes in density and adhesion. While the chemical content was characterized using HPLC and FTIR. The extraction process includes drying to grinding the bintaro seeds into powder, followed by extraction using a ratio of bintaro powder and 96% (m/v) ethanol 1:3. Bitaro extract obtained was added to commercial watercolors (100 ml) with variations of 5, 10 and 15 ml. The paint is applied to the surface of the multiplex wood evenly by pre-heating it at 40°C. The adhesion analysis was carried out using the help of ImageJ software to determine the ratio of the gray value of the image before and after the adhesion test using the cross-cut technique. It was observed that the increase in bintaro seed extract caused a decrease in paint adhesion.